Eco-Demographic Changes and Labour Supply Growth in Greece / Studies 24 - Athanassiou Stylianos C.; Centre Of Planning And Economic Research (1986)
Theoretical Survey of Labour Supply Growth, Theories Related to Present Study, Labour Supply (Economically Active Population), Demographic Factors of Labour Supply Growth, Impact of Social and Economic Factors on the Labour Supply, Empirical Analysis of Labour Supply Growth, Population, Labour Supply (Economically Active Population), Economically Inactive Population, Assessment of the Demographic and Socio-Economic Factors Affecting the Labour Supply Growth, Appendix I and II, References.